Exploring the causal role of gut microbiota in giant cell arteritis: a Mendelian randomization analysis with mediator insights - Wu, Menglin; Liao, Zhixiong; Zeng, Kaidong; Jiang, Qiaohui (Frontiers in Immunology, 2024)
Giant Cell Arteritis (GCA) is a complex autoimmune condition. With growing interest in the role of gut microbiota in autoimmune diseases, this research aimed to explore the potential causal relationship between gut microbiota and GCA, and the mediating effects of specific intermediaries.Using a bidirectional two-sample Mendelian randomization(MR) design, we investigated associations between 191 microbial taxa and GCA. A two-step MR technique discerned the significant mediators on this relationship, followed by Multivariable MR analyses to quantify the direct influence of gut microbiota on GCA and mediation effect proportion, adjusting for these mediators.Nine taxa displayed significant associations with GCA. Among them, families like Bacteroidales and Clostridiaceae1 had Odds Ratios (OR) of 1.48 (p=0.043) and 0.52 (p=5.51e-3), respectively. Genera like Clostridium sensu stricto1 and Desulfovibrio showed ORs of 0.48 (p=5.39e-4) and 1.48 (p=0.037), respectively.Mediation analyses identified 25 hydroxyvitamin D level (mediation effect of 19.95%), CD14+ CD16-monocyte counts (mediation effect of 27.40%), and CD4+ T cell counts (mediation effect of 28.51%) as significant intermediaries.Our findings provide invaluable insights into the complex interplay between specific gut microbiota taxa and GCA. By highlighting the central role of gut microbiota in influencing GCA risk and long-term recurrence, and their interactions with vital immune mediators, this research paves the way for potential therapeutic interventions in GCA management.